Digest of the Charters and Ordinances of the City of Memphis, Together with the Acts of the Legislature Relating to the City, with an Appendix, Ch. 13, Art. III., at 190 (October 7, 1863) (WM. H. Bridges, Argus Book and Job Office 1863) - (:unkn) unknown (My University, 1863)
Prohibited the carrying of a concealed pistol, Bowie knife, dirk, or any other deadly weapon. Punishable by fine of $10-50.
Keywords: CARRY - CONCEALED